1971
DOI: 10.1002/pssb.2220470234
|View full text |Cite
|
Sign up to set email alerts
|

Exciton–exciton annihilation in pyrene crystals

Abstract: Specific features of the exciton+xciton annihilation process for slow diffusion systems are considered in terms of excimer luminescence in pyrene crystals. I n this case luminescence decay curves allow a direct determination of the diffusion coefficient and the mean free path of the excitation during its lifetime. Analogy between excimer excitations and the well-known slow excitons is discussed. The importance of the experimental separation of excinier and monomer excitons whose kinetic parameters are greatly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
7
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
3
7
0
Order By: Relevance
“…The most intense vibronic band of the dimeric ST exciton in a shallow trap or Y state appears at 535 nm for α-perylene crystals and this emission is very weak at room temperature but at temperatures <77 K, intensity increases in compensation with that of E-emission. , In the perylene crystals, the most intense component around 526 nm (19,000 cm –1 ) of the defect emission corresponds to the 0–1 band of the perylene monomer emission, while the 0–0 band appears at 500 nm (20,000 cm –1 ) and its intensity is considerably reduced by reabsorption . Thin films, nanocrystals, or nanoaggregates (thickness or sizes < 300 nm) have a large number of the monomer defect sites and hence the defect emission may be expected to be observed easily by the steady-state excitation at temperatures below 77 K or time-resolved emission spectroscopy with time resolution better than a few ns . Monomer defect emission has also been observed in the case of pyrene films or nanocrystals. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most intense vibronic band of the dimeric ST exciton in a shallow trap or Y state appears at 535 nm for α-perylene crystals and this emission is very weak at room temperature but at temperatures <77 K, intensity increases in compensation with that of E-emission. , In the perylene crystals, the most intense component around 526 nm (19,000 cm –1 ) of the defect emission corresponds to the 0–1 band of the perylene monomer emission, while the 0–0 band appears at 500 nm (20,000 cm –1 ) and its intensity is considerably reduced by reabsorption . Thin films, nanocrystals, or nanoaggregates (thickness or sizes < 300 nm) have a large number of the monomer defect sites and hence the defect emission may be expected to be observed easily by the steady-state excitation at temperatures below 77 K or time-resolved emission spectroscopy with time resolution better than a few ns . Monomer defect emission has also been observed in the case of pyrene films or nanocrystals. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Luminescence of both free (F) and self-trapped (ST) excitons (henceforth they will be designated as dimeric excitons) have been observed in both α-pyrene and α-perylene crystals at low temperature (say, below 50 K). In these crystals at room temperature, delocalized free excitons generated by photoexcitation are rapidly relaxed into ST excitons because of strong exciton–phonon interaction. , ST excitons are considered as excimers, which emit spectrally red-shifted, broadened excimer luminescence, which is a forbidden transition. A two-step excimer formation mechanism has been proposed from the results of temperature-dependent fluorescence studies as well as ultrafast dynamics studies. ,, However, only a few of these studies reported migration dynamics of excitons in these crystals, probably because of rapid relaxation of free excitons into excimers (within a few ps), which prevents excitons from being propagated even over a few nanometers. ,,,, In contrast to the concept that molecular excimers are trapped states and hence should be immobile, Pensack et al revealed that the excimer was diffusive and considered as a singlet exciton. ,, However, it is now well understood that diffusivity of the dimeric excitons is much slower than that of the monomeric excitons because the resonance energy transfer process involving ST excitons must be accompanied by intermolecular structural changes that can cause the diffusion process to be thermally activated. ,,,, On the other hand, the monomeric excitons populated in the β-form of the crystals have larger mobility. ,, …”
Section: Introductionmentioning
confidence: 99%
“…We may say that exciton diffusion in the crystal is a unique catalyst which maintains the exciton-exciton annihilation process and i s essential for observing the non-linear quenching process. Such explanation suggests that a similar effect will be observable in all crystals with small diffusion length where, a s shown in(1) , non-linear quenching i s associated with diffusion energy migration.Nevertheless it is impossible to eliminate the effect of other exciton processes which occur in case of steady-state conditions and are absent in decay kinetics of this phenomenon. In particular a further study of exciton reabsorption of exciting light quantum i s required.…”
mentioning
confidence: 73%
“…In the present note we continue our study of the exciton-exciton annihilation process in pyrene crystals which was started in (1). The temperature dependence of noii;linear luminescence quenching in pyrene crystals in the temperature range from 77 to 373 were described in detail in (1). Nonlinear quenching was studied for five fixed temperatures: T = 77, 153, 223, 293, and 373 K , for which quenching kinetics and relatiire quantum yield of steady-state luminescence versus excitation intensity were determined.…”
mentioning
confidence: 79%
See 1 more Smart Citation